ANALISIS KONTRIBUSI PENDAPATAN USAHATANI SAYURAN DAUN TERHADAP PENDAPATAN RUMAH TANGGA (Studi Kasus : Petani Sayuran Daun Binaan Dinas Pertanian dan Peternakan Provinsi Riau di Kota Pekanbaru) - Surya Ningsih; Yusmini Yusmini; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2016)
The purpose of this reseach was to analyzed the leaf vegetable farm income, household income of vegetable growers and analyze the contribution of leaf vegetable farmers' income. This reseach used 9 (nine) population assisted leaf vegetable farmers of Agriculture and Livestock of Riau Province. The research method used survey method, to perform the analysis of farm income, household income and contribution formula wass the formula used some production costs, equipment depreciation, farm income, household income, as well as revenue. The results showed that the average net income per season vegetable farming Rp.5.783.611,86/ leaf plant, with total costs amounting to Rp.12.573.610,37/season planting. The average household income was obtained by Rp.5.100.853,93/month, derived from vegetable farming income amounted Rp.2.955.483,86/month and other revenues amounted to Rp.2.145.370,07/month. The average contribution of leaf vegetable farm income to household income is 57.93% or by Rp.2.955.483,86 included in the high category. The growing season for all commodities leaf vegetables in this study are assumed to have the same time frame that is 90 days or 3 months.